Mono‐Active Bimetallic Oxide Co2AlO4 with Yolk‐Shell Structure as a Superior Lithium‐Storage Material. Issue 13 (2nd July 2019) - Zeng, Kewen; Tan, Lei; Li, Xinhai; Wang, Zhixing; Guo, Huajun; Wang, Jiexi; Yan, Guochun
Abstract: The mono‐active bimetallic oxide Co2 AlO4 with microsphere morphology and yolk‐shell structure are synthesized and first evaluated as anode materials for lithium ion batteries. The electrochemically inactive Al element disperse well in the material at an atomic‐scale level, which can effectively alleviate volume expansion during the cycling and heighten the electrochemical reaction kinetics. Moreover, the yolk‐shell structure provides adequate buffer space for volume expansion. Benefited from the synergy effect of the yolk‐shell structure and uniformly element Al distribution, the yolk‐shell Co2 AlO4 delivers a discharge capacity of 661 mAh g −1 at 1000 mA g −1 after 500 cycles with a capacity retention ratio of 86.4 %, and maintains a high discharge capacity of 548 mAh g −1 at 3200 mA g −1, showing excellent long‐term cycle performance and rate capability. Abstract : Electrode materials : The mono‐active bimetallic oxide Co2 AlO4, with microsphere morphology and yolk‐shell structure, is synthesized and evaluated as anode material for lithium‐ion batteries. The electrochemically inactive Al species are well dispersed throughout the material at an atomic‐scale level, which can effectively alleviate volume expansion during cycling and favor the electrochemical reaction kinetics. Moreover, the yolk‐shell structure provides adequate buffer space for volume expansion.